The human source memory system struggles to distinguish virtual reality and reality - Marius Rubo (Elsevier, 2021)
Virtual Reality (VR) is used in a variety of fields with the goal to increase ecological validity compared to traditional monitor-based setups. Here we report additional evidence for the adequacy of this research strategy. In a memory confusion paradigm spanning over stimuli presentation in reality, VR and on a computer monitor, participants were more prone to confusing reality with VR than with a traditional monitor-based setup, indicating a relative proximity of experiences in VR and reality. We speculate that the human source memory's difficulty in distinguishing VR from reality may provide a basis for the good generalizability of treatment effects in VR to daily life. At the same time, the effect may demonstrate a potential danger of a mindless use of VR technology.